Project-Based Learning for Enhancing Students' Speaking Skills - Sri Wahyuni; Nunung Anugrawati; Firman (FKIP Unismuh Makassar, 2026)
Developing students' English speaking skills remains a major challenge in secondary education, requiring innovative instructional approaches that promote authentic communication. This study examined the effectiveness of Project-Based Learning (PBL) in improving the speaking skills of Grade XI students at UPT SMA 2 Jeneponto using a pre-experimental research design. The novelty of this study lies in integrating video dubbing of narrative texts as a project-based speaking task to enhance students' fluency and vocabulary. Data were collected through pre-test and post-test assessments. The findings revealed significant improvements in students' speaking performance, with fluency scores increasing from 29.19 to 65.58 and vocabulary mastery showing substantial gains. Statistical analysis confirmed a significant effect of PBL on speaking achievement (p = 0.000 < 0.05), leading to the acceptance of the alternative hypothesis. This study contributes empirical evidence that PBL is an effective, student-centered approach for fostering speaking proficiency and communicative confidence in English classrooms.